2018
DOI: 10.1002/jcp.27885
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs in cancer stem cells: Biology, pathways, and therapeutic opportunities

Abstract: Cancer stem cells (CSCs) are a small subpopulation of tumor cells that have been identified in most types of cancer. Features that distinguish them from the bulk of tumor cells include their pluripotency, self‐renewal capacity, low proliferation rate, and tumor‐initiating ability. CSCs are highly malignant, as they confer drug resistance and facilitate tumor progression, relapse, and metastasis. The molecular mechanisms underlying CSC biology are now beginning to be understood. In this context, microRNAs (miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 169 publications
0
57
0
Order By: Relevance
“…Numerous studies have shown that miRNAs are evolutionarily conserved and are key regulators of diverse biological processes such as development, cell proliferation and differentiation, apoptosis and metabolism [61]. MiRNAs also have important regulatory roles in disease progression, including oncogenesis [62, 63]. The molecular mechanisms that control miRNA expression are therefore of critical importance in better understanding normal physiologic processes and disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that miRNAs are evolutionarily conserved and are key regulators of diverse biological processes such as development, cell proliferation and differentiation, apoptosis and metabolism [61]. MiRNAs also have important regulatory roles in disease progression, including oncogenesis [62, 63]. The molecular mechanisms that control miRNA expression are therefore of critical importance in better understanding normal physiologic processes and disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms that control miRNA expression are therefore of critical importance in better understanding normal physiologic processes and disease pathogenesis. Recently, DNA methylation has emerged as a key regulatory mechanism of miRNA expression in several different tissues and disease states [6265].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have shown the critical roles of ncRNAs in CSCs biology [13][14][15][16][17][18][19][20][21][22]. Accumulating evidence has provided insights into the importance of ncRNAs as regulators in several critical steps of cancer development, such as carcinogenesis, cancer invasion, and metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 6: miRNAs in regulating cancer stem cells characteristics Key microRNAs have been described to affect the main signaling pathways regulating CSCs. It was for example showed that different microRNAs affect [14]: -Wnt signaling → for instance miR-600 or miR-217 -Notch signaling → miR-34a or miR-141 -Hedgehog signaling → miR-324-5p or miR-326 miRNAs are key intracellular regulators of gene expression and play roles in tumor initiation and distant metastasis via controlling CSCs properties. Some of these miRNAs have tumor suppressor properties, whereas others act as oncogenes [13].…”
Section: Micrornas and Cancer Stem Cellsmentioning
confidence: 99%
“…In CRC, differential miRNA expression has been related to stage and site of the tumor [11]. Mounting evidence also indicates a role for miRNAs in the maintenance of the CSC phenotype [12][13][14][15][16]. We have been focusing on miRNAs that contribute to maintenance of the phenotype of colonic CSCs.…”
Section: Introductionmentioning
confidence: 99%